Economizing justice: Turning equity claims into lower energy tariffs in Chile. (June 2017) - Alvial-Palavicino, Carla; Ureta, Sebastián
Abstract: This paper considers the issue of how energy justice is economized; how political and ethical claims about particular energy (in)justices are turned into economic valuations. Drawing on science and technology studies, we present a conceptual framework that understands economization as emerging from three interrelated processes: problematization, framing and overflowing. Applying this framework to the drafting of new energy legislation in Chile, we trace how perceived shortcomings in equity and distributional justice were turned into "market failures, " able to be resolved by market-based mechanisms. This case highlights the dangers implicit in the uncritical economization of energy justice claims, in which ethical considerations regarding the distribution of risks and benefits of energy production and provision are reduced to a redistribution of payments among consumers – something that limits the possibilities for structural reform. Highlights: The implementation of an electricity equity tariff is discussed. A process of economization transforms equity demands into market devices. Energy justice, as mobilized in the policy process, includes multiple forms of justice. Competition between these multiple forms fails to deliver a complete form of justice.